Research of Victoria Blue B Wastewater by Coagulation and Co-Precipitation - Wang, Yanhua; Gao, Chanjuan; Yang, Shengke (Asian Journal of Chemistry, 2014)
Dying industrial wastewater has become a major problem in the modern industrial water treatment, owing to their complex structures, bio-refractory, anti-oxidation, anti-photolysis and strong heat stability. Thus, treatment of dye wastewater has attracted the attention of researchers all the time. The focus of this work is removal effect of 2,4,6-trimercaptotriazine and aluminum sulfate independent action and synergistic effect on Victoria blue B. The removal effect with different factors, such as the dosage of 2,4,6-trimercaptotriazine or aluminum sulfate, pH value, temperature and other conditions, were investigated and the removal mechanism was discussed. The results show that the decolour treatment of Victoria blue B dye wastewater can achieve the ideal effect by the synergistic effect of 2,4,6-trimercaptotriazine and aluminum sulfate.